NRF2 antioxidant response protects against acidic bile salts-induced oxidative stress and DNA damage in esophageal cells. (28th August 2019) - Peng, Dunfa; Lu, Heng; Zhu, Shoumin; Zhou, Zhangjian; Hu, Tianling; Chen, Zheng; Zaika, Alexander; El-Rifai, Wael
Abstract: Gastroesophageal reflux disease (GERD) is the main risk factor for Barrett's tumorigenesis. In this study, we investigated the role of NRF2 in response to exposure to acidic bile salts (ABS), in conditions that mimic GERD, using Barrett's esophagus cell models. We detected an increase in NRF2 protein levels, following exposure to ABS. We found oxidization of cysteines (cysteines with oxidized thiol groups) in KEAP1 protein with a weaker interaction between NRF2 and KEAP1, following ABS exposure. Treatment with bile salts increased nuclear NRF2 levels, enhancing its transcription activity, as measured by an ARE (antioxidant response element) luciferase reporter assay. The mRNA expression levels of NRF2 target genes, HO-1 and GR, were increased in response to ABS exposure. Using genetic overexpression and knockdown of NRF2, we found that NRF2 has a critical role in suppressing ABS-induced ROS levels, oxidative DNA damage, DNA double strand breaks, and apoptosis. Collectively, our results suggest that transient induction of NRF2 in response to ABS plays a pivotal role in protecting esophageal cells by maintaining the levels of oxidative stress and DNA damage below lethal levels under GERD conditions. Highlights: Gastroesophageal reflux disease (GERD) is the main risk factor for esophageal Barrett's tumorigenesis. Using conditions that mimic GERD, we demonstrate transient induction of NRF2 in response to acidic bile salts (ABS). Acidic bile salts induced oxidation of KEAP1, with release and nuclear accumulation of NRF2. Activation of NRF2 protected esophageal cells by suppressing ABS-induced ROS, DNA damage and apoptosis.